PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X SMA TAMAN RAMA DENPASAR - I Made Surat; I Dewa Putu Juwana (Widyadari, 2023)
The problem-based learning model is a learning model that presents a problem that is closely related to the real world, especially in students' daily lives. The purpose of this study was to determine the effect of applying the Problem Based Learning learning model on students' critical thinking skills in trigonometry learning at 10 SMA Taman Rama students. The population in this study were all students of SMA Taman Rama class X for the academic year 2023/2024, totaling 79 students. The sampling technique in this study used simple random sampling. The sample in this study was 40 students by taking 2 classes, namely class 10.1 as an experimental class totaling 19 students and class 10.2 as a control class totaling 21 students. This research instrument uses a test sheet. Data analysis techniques in this study used prerequisite tests and hypothesis testing. The results showed that the application of the problem-based learning learning model had an effect on students' critical thinking skills, because the results of the t-test analysis obtained a significance value (sig.2-tailed) of 0.000 <0.05, then Ha was accepted and Ho was rejected. The results of data analysis obtained on average after being given treatment using the problem-based learning model in the experimental class, namely 80.5. Meanwhile, students in the control class on average without being given a problem-based learning model were 72.5.